Synthesis of 2-Pyrones from Renewable Resources - Dobler, Daniel; Leitner, Michael; Kreitmeier, Peter; Reiser, Oliver (Synthesis, 2023)
An atom-economic reaction sequence on a multigram scale for synthesizing 2-pyrone was developed starting from furfuryl alcohol, a renewable resource made from bran or bagasse, utilizing a large-scale thermal rearrangement of cyclopentadienone epoxide as the key step. Additionally, 6-substituted 2-pyrone natural product derivatives are readily accessible by this approach.
Keywords: pyrone; furfural; furfuryl alcohol; renewable resources; Piancatelli rearrangement; flash vacuum pyrolysis